2011
DOI: 10.1016/j.materresbull.2011.07.041
|View full text |Cite
|
Sign up to set email alerts
|

New type of incommensurate magnetic ordering in Mn3TeO6

Abstract: The complex metal oxide Mn3TeO6 exhibits a corundum related structure and has been prepared both in forms of single crystals by chemical transport reactions and of polycrystalline powders by a solid state reaction route. The crystal structure and magnetic properties have been investigated using a combination of X-ray and neutron powder diffraction, electron microscopy, calorimetric and magnetic measurements. At room temperature this compound adopts a trigonal structure, space group R3 with a = 8.8679(1) {\AA},… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
54
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 25 publications
(32 reference statements)
4
54
0
1
Order By: Relevance
“…Rietveld refinements of the NPD data at 295 K confirmed the XRD result that the crystal structure of the Mn 1.5 114 Cd 1.5 TeO 6 sample is the same as that of Mn 3 TeO 6 [2,3]. No vacancies were observed in the cationic or in the anionic substructures.…”
Section: Neutron Powder Diffraction At Room Temperaturesupporting
confidence: 65%
See 1 more Smart Citation
“…Rietveld refinements of the NPD data at 295 K confirmed the XRD result that the crystal structure of the Mn 1.5 114 Cd 1.5 TeO 6 sample is the same as that of Mn 3 TeO 6 [2,3]. No vacancies were observed in the cationic or in the anionic substructures.…”
Section: Neutron Powder Diffraction At Room Temperaturesupporting
confidence: 65%
“…The 2 K NPD pattern shows the presence of additional small broad peaks of magnetic origin (see Figures 5 and 6) that has to be taken into account in the refinement. A magnetic structure for Mn 1.5 114 Cd 1.5 TeO 6 was refined taking the magnetic structure reported earlier for Mn 3 TeO 6 [3] as a starting point and, in fact, this same model adequately describes also the magnetic structure of the magnetically diluted sample, Mn 1.5 114 Cd 1.5 TeO 6 . The magnetic Bragg peaks could not be indexed using simple multiples of the crystallographic unit cell, implying that the magnetic structure is incommensurate with respect to the nuclear structure of the crystal.…”
Section: Low Temperature Neutron Powder Diffractionmentioning
confidence: 97%
“…Mn 3 TeO 6 shows complex incommensurate spin ordering 28 , and magnetically induced improper ferroelectricity has recently been reported in Co 3 TeO 6 (refs 29,30). Owing to its complex magnetic phase diagram, the origin of the electric polarization in Co 3 TeO 6 is still under debate.…”
mentioning
confidence: 87%
“…19 ] Neutron powder diffraction experiments on crushed single crystals in the temperature range 1.6-295 K suggest a magnetic structure involving several propagation vectors. 12 The evolution of diffraction patterns with temperature clearly showed that the strongly distorted monoclinic phase remained at all temperatures. Nevertheless, it was found that around 18-25 K some shifts of diffraction peaks could be registered, indicating possible magnetostrictive phenomena.…”
mentioning
confidence: 96%
“…9 Mn 3 TeO 6 , on the other hand, was recently reported to exhibit a complex incommensurate spin structure, consisting of two different magnetic orbits. 10 The magnetic and electrical properties of Co 3 TeO 6 are unknown to date, although its structure shows some interesting features which may strongly influence its magnetic ordering. There are five distinguishable sites for the magnetic Co 2+ cations and the Co-O bond length varies greatly from 1.97 to 2.93Å.…”
mentioning
confidence: 99%